On Total Product Cordial Labeling of Some Crown Graphs - Ariel C. Pedrano; Ricky F. Rulete (International Journal of Mathematics And its Applications, 2017)
A total product cordial labeling of a graph G is a function f:V → {0,1}. For each xy, assign the label f(x)f(y), f is called total product cordial labeling of G if it satisfies the condition that |v_f(0)+e_f(0)-v_f(1)-e_f(1)|≤ 1 where v_f(i) and e_f(i) denote the set of vertices and edges which are labeled with i=0,1, respectively. A graph with a total product cordial labeling defined on it is called total product cordial. In this paper, we determined the total product cordial labeling of P_m ° C_n, P_m ° P_n, C_m ° P_n, P_m ° F_n, P_m ° W_n and P_m ° K_n.